Analysis of Opportunities and Challenges of Indonesian Agricultural Product Trade with Australia: Case Study in the APEC Framework - Mela Aprillia; Daspar (JISOSEPOL: Jurnal Ilmu Sosial Ekonomi dan Politik, 2025)
Agricultural trade between Indonesia and Australia holds strategic importance in supporting national food security and expanding access to global markets. This study aims to examine the opportunities and challenges faced by Indonesia in enhancing agricultural exports to Australia under the framework of the Asia-Pacific Economic Cooperation (APEC). Using a descriptive qualitative method and secondary data from government institutions, international organizations, and academic sources, the study finds that export opportunities are largely driven by product complementarity and trade liberalization initiatives. Nevertheless, technical barriers such as Australia’s stringent biosecurity regulations and quality standard discrepancies remain key obstacles. Therefore, improving product quality, engaging in proactive economic diplomacy, and strengthening export infrastructure are vital strategies to boost Indonesia’s agricultural competitiveness in the Australian market.